Base management of information with scada for the automated control of a valve of proportional control - Poma Deza, Jorge (2011)
This article discusses the importance and applications of the Database Management in Automated Processes, with the objective of to make a good control of the production and human resources, maintenance of the devices, processing of information for an adapted making decisions and the improvement of the Industrial Proccesses. To show the interaction software-hardware have been designed applications with Intouch Software during “I Curso Internacional de Supervisión y Automatización totalmente integrada” (SENA-Colombia), Microsoft SQL Server at the Centro de Manufactura Avanzada (CEMA-UNMSM) and LABVIEW in the company Equipment & Systems for Advanced Technology SAC (E-SAT PERU) and different hardware